2017
DOI: 10.1530/erc-16-0493
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive decline in prostate cancer patients undergoing ADT: a potential role for exercise training

Abstract: Androgen deprivation therapy (ADT) is an effective and widely prescribed treatment for prostate cancer (PCa), but it is associated with multiple treatment-induced adverse effects that impact on various musculoskeletal and cardiometabolic health outcomes. Emerging research has shown that ADT is also associated with cognitive impairment, which has been linked to a loss of independence, increased falls and fracture risk and greater use of medical services. The aim of this review is to outline the evidence related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 71 publications
0
21
0
Order By: Relevance
“…It has been found that in the treatment period of the disease there are consequences for the physical health of the patient, such as fatigue, insomnia, nausea and vomiting, pain, dyspnea, constipation, diarrhea, urinary and intestinal symptoms and urinary incontinence 8,9 . In the present study, the symptomatic scale of both the general and specific questionnaire for men with prostate cancer revealed that worst results were related to the presence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that in the treatment period of the disease there are consequences for the physical health of the patient, such as fatigue, insomnia, nausea and vomiting, pain, dyspnea, constipation, diarrhea, urinary and intestinal symptoms and urinary incontinence 8,9 . In the present study, the symptomatic scale of both the general and specific questionnaire for men with prostate cancer revealed that worst results were related to the presence of depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Among the modalities of treatment for prostate cancer, radical prostatectomy, in which the patient undergoes complete removal of the prostate, is the oldest and possibly the most effective 7 . Such a method can cause several side effects, such as urethral stenosis, urinary incontinence, erectile dysfunction 5 , fatigue, general distress, functional disability and depression 8,9 , factors that can significantly affect the quality of life of such men 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that ADT use is associated with cognitive decline, particularly in the domains of verbal memory, visuomotor function, attention and executive function [ 80 ]. Thus, this study will include a number of established and valid cognitive tests to assess the different cognitive domains.…”
Section: Methodsmentioning
confidence: 99%
“… 2 However, long-term deprivation of androgen may cause some systemic adverse effects, such as metabolic complications and cardiovascular disease. 3 – 7 Alterations to the immune system in patients with ADT were also noted. 8 , 9 Increased risk of rheumatoid arthritis in patients with ADT has also been observed.…”
Section: Introductionmentioning
confidence: 99%